"One of ours" - an exploration of inclusion and the use of alternative provision - Brown, Zoe Louise (2018)
The research presented here is an exploratory investigation of the attitudes of key decision-makers towards the placement of young people with social, emotional, mental health difficulties (SEMH) in alternative provisions. These attitudes were explored in the context of the participants’ definitions of and attitudes towards inclusion alongside further exploration of factors which both help and hinder the inclusion of young people who attend these settings. Literature surrounding inclusion, exclusion, alternative provisions and teacher attitudes towards young people with SEMH informed the development of the study, alongside literature concern the theory of attitudes.